Zeb1 potentiates genome‐wide gene transcription with Lef1 to promote glioblastoma cell invasion - Rosmaninho, Pedro; Mükusch, Susanne; Piscopo, Valerio; Teixeira, Vera; Raposo, Alexandre ASF; Warta, Rolf; Bennewitz, Romina; Tang, Yeman; Herold‐Mende, Christel; Stifani, Stefano; Momma, Stefan; Castro, Diogo S (The EMBO journal, 2018)
Glioblastoma is the most common and aggressive brain tumor, with a subpopulation of stem‐like cells thought to mediate its recurring behavior and therapeutic resistance. The epithelial–mesenchymal transition (EMT) inducing factor Zeb1 was linked to tumor initiation, invasion, and resistance to therapy in glioblastoma, but how Zeb1 functions at molecular level and what genes it regulates remain poorly understood. Contrary to the common view that EMT factors act as transcriptional repressors, here we show that genome‐wide binding of Zeb1 associates with both activation and repression of gene expression in glioblastoma stem‐like cells. Transcriptional repression requires direct DNA binding of Zeb1, while indirect recruitment to regulatory regions by the Wnt pathway effector Lef1 results in gene activation, independently of Wnt signaling. Amongst glioblastoma genes activated by Zeb1 are predicted mediators of tumor cell migration and invasion, including the guanine nucleotide exchange factor Prex1, whose elevated expression is predictive of shorter glioblastoma patient survival. Prex1 promotes invasiveness of glioblastoma cells in vivo highlighting the importance of Zeb1/Lef1 gene regulatory mechanisms in gliomagenesis. Synopsis Genome‐wide characterization of Zeb1 transcriptional targets in glioblastoma stem cells reveals how Zeb1 coordinately regulates an EMT‐like program, simultaneously promoting gene activation and repression via two different mechanisms. ChIP‐seq mapping correlates transcriptional repression with direct Zeb1 binding to gene regulatory regions. Indirect recruitment mediated by Lef/Tcf factors potentiates gene expression independent of Wnt signaling. Activated genes include regulators of cell migration and invasion that correlate with Zeb1 expression in tumors. Zeb1 activates Prex1 to promote glioblastoma cell invasion in vivo . Graphical Abstract Genome‐wide binding reveals that the EMT‐inducer Zeb1, best‐known as a transcriptional repressor, can team up with a transcriptional activator to indirectly enhance gene expression.